PENGARUH KEPEMIMPINAN DAN KECERDASAN SPIRITUAL TERHADAP KINERJA KARYAWAN - Nurdin Nurdin (POLITEKNIK LP3I JAKARTA, 2012)
The objective of this research is to find out the influence of leadership and spiritual quotient to the employee performance. Data was collected by sending about 34 questionnaires data to all of employees in Politeknik LP3I Jakarta, Gedung Sentra Kramat Jl. Kramat Raya No.7-9 Jakarta Pusat 10450 Indonesia. This research used survey, sampling method and questionnaires as tools in collecting the main data with a quantitative method. This research used simple random and sampling technique. Data were analyzed by Software SPSS verse 17 for Windows.The results of this research show that: 1) The leadership influences the employee performance significantly; 2) The spiritual Quotient influences the employee performance significantly; and 3) The leadership and spiritual quotient simultaneously have a significant influence to employee performance. It is important for any one whose job is as a decision maker in management structure to understand the leadership as one of variables influences the employee performance; and also, the spiritual quotient.Key words: Leadership, Spiritual Quotient, and Employee’s, Performance